Orolingual angioedema to alteplase. Identify, counsel and monitor at risk patients. (2nd September 2016) - Timmis, Christopher; Epstein, Elliot; Salim, Mohmad
Abstract : Orolingual angioedema (OLA) is a known complication of intravenous alteplase used to treat ischaemic stroke. The incidence may be as high as 5.1%. ACE inhibitors are thought to increase the risk of developing this potentially life-threatening complication. This case report demonstrates how we may improve in the identification of risk factors in the history; the counselling of patients appropriately; in seeking alternative therapies such as mechanical thrombectomy; and in the monitoring of patients for signs of OLA once alteplase has been given.